Factors for not performing a vaginal delivery: systematic review (Research, Society and Development, 2022)
Brazil is experiencing an epidemic of cesarean surgery, statistically surpassing the world level. In this sense, WHO declares that the ideal rate for cesarean sections is approximately 10 to 15%, with no justifiable condition in any region of the world for the rate to be higher than this. In this perspective, Brazil has the aforementioned rate of approximately 56%, with the public service being 40%, therefore, it is one of the countries targeted as a precursor of abusive cesarean deliveries. Objective: To review the factors that influence the non-accomplishment of vaginal delivery, based on maternal behavior and professional assistance, in the Brazilian Unified Health System (SUS). Methodology: Systematic review of studies published in LILACS, MEDLINE and BDENF databases using descriptors (normal delivery, cesarean delivery, maternal behavior, health professional and Brazil) cataloged in DeCS, in articles published from 2016 to 2021. Results: 06 articles were analyzed. Based on maternal behavior, the fear factor is the main contributor to the non-accomplishment of vaginal delivery; on the other hand, when related to professional assistance, the decision factor is highlighted. Most of the studies were carried out in the Northeast region, and the Midwest and North regions did not have research in this line of content. Final considerations: Among the factors found, all are committed to a context of reality, which may be related to experiences/assistance in prenatal, childbirth and/or puerperium times, in the context of experiencing vaginal birth and/or cesarean surgery.